Complete Transection of Main Bile Duct during Laparosopic Cholecystectomy : Experiences in Chaoprayayomraj Hospital, Suphan Buri - Changsrisuk, Somdej (Journal of Health Science of Thailand, 2017)
Among various of complications of laparoscopic cholecystectomy, the main bile duct transection is the most rare and critical. This case report included 6 patients of complete bile duct transection in the 810 patients operated in Chaoprayayomraj Hospital since 1966. Three of them were diagnosed immediately during the operation and the other three patients were diagnosed in the postoperative periods. Oftenly the diagnosis was difficult during the operation. Appropriate treatments depended on timing of diagnosis and types of injuries. For patients diagnosed during operation, immediate repair should be done. This report showed a case of end-to-end anostomotic repair and two of Roux-en-y choledochojejunostomy. The patients diagnosed postoperatively were repaired in early and late stage after the investigations were done. Obstructed bile duct patient should be repaired within 2-3 weeks and bile leakage patient in 3-5 months later, after the general conditions of the patient improved. This report had 3 patients diagnosed postoperatively, two obstructed bile duct and one bile leakage, early repair were done by Roux-en-y hepaticojejunostomy with difficulties. Long-term followed up in 5 patients had good results except in the bile-leakage patient who died postoperatively from septicemia and renal failure. Reconstruction should be accomplished by experienced surgeon. If the surgeon is not experienced in hepatobiliary repair, adequate drain should be done and then refered the patient to appropriate hepatobiliary center without delay. Sucessful operative repair requires healthy, non ischemic bile duct, a tension-free and mucosato- mucosa anastomosis. This complication will occur despite every effort to prevent by the surgeon. To combat errors and prevent complications, surgeon should heighten vigilance during dissection of the Calot’s triangle and learned more to improve the surgical technique.